Using written, audio, and video vignettes to translate knowledge to elite strength and conditioning coaches - Szedlak, C.; Smith, M. J.; Callary, B.; Day, M. C. (International Sport Coaching Journal, 2019)
Research has shown that vignettes are useful in disseminating complex and applied information to practitioners with research mainly utilising written and audio vignettes to disseminate good practice. The current study examined the utility of a research-based vignette, presented in different formats (written, audio, video), to disseminate information to elite strength and conditioning (S&C) coaches. A single vignette was developed in three formats: a written, an audio, and a video vignette. The vignette involved an experienced S&C coach as the main character, and the plot outlined how this S&C coach aimed to learn more about effective coaching. Nineteen elite S&C coaches reflected on the utility of different vignette formats. Data were analysed using a thematic analysis. Overall, the results suggest that vignettes are useful in translating knowledge and encourage action, regardless of which format is used. Furthermore, the S&C coaches reported a preference for the video format, due to the video`s ability to communicate emotional, verbal and non-verbal behaviours. Practically, the vignette prompted the S&C coaches to reflect on areas such as coaching philosophy and values resulting in initial changes in their coaching practice.